Design and analysis of truss-beam steel-shuttering jumbo for tunnel lining based on CAD/CAE. (1st January 2011) - Peng, Weiping; Yang, Bin; Liu, Zhao; Wang, Daoming
The truss-beam steel-shuttering jumbo is the key construction equipment for tunnel lining, which is usually designed for customisation according to the shape and size of the tunnel, and which must satisfy the requirements of intensity, rigidity and supporting stability. Aiming at the insufficiency of existing methods in the jumbo design, the CAD/CAE technology is introduced into the domains of the jumbo design. With Pro/E, the parametric modelling of the truss-beam steel-shuttering jumbo for diversion tunnel lining in Xiluodu hydropower station is completed, virtual assembly is established based on three-dimensional digital model, and motion simulation is implemented for detecting whether there are interferences in structure and working of the jumbo. And the stress and strain of the jumbo under different working conditions are analysed by ANSYS for verifying the design feasibility and structural reliability of the jumbo. Meanwhile the results of finite element analysis provide a basis for the structure optimisation of the jumbo.